Development sites and early stages of eleven species of Clusiidae (Diptera) occurring in Europe - Rotheray, Graham E; Horsfield, David (Zootaxa, 2013)
Two hundred and ninety-six rearing records of 11 clusiid species (Diptera, Clusiidae) were obtained from 8 tree species in England, Finland, France, Norway, Russiaand Scotland, mainly during the period 1994 to 2004. Larvae and puparia were found between annual layers of whitewood (sapwood and heartwood) of wet, decay-softened, dead wood. Levels of host tree specificity were low, most species were reared from 2–4 host trees, maximum 6. The clusiid larva is distinguished by: a small, translucent head skeleton with an obliquely-shaped apex to the artium; a pseudocephalon fixed in an inverted position except for an external, flattened section bearing the antennomaxillary organs; a spherical prothorax with a truncate rim embedded with sensilla and, a wedge-shaped anal segment bearing a pair of conspicuous, sclerotised, red-brown hooks on the inner margins of which are the posterior spiracular plates. Many of these features support a distinctive feeding mechanism, spot-sucking of biofilm coating wet, decaying whitewood. Early stage characters support the results of recent supraspecific taxonomic and systematic investigations, such as the synonymy of Paraclusia Czerny under Clusia Haliday and the recognition of species groups in Clusiodes Coquillett. Based on early stages, supraspecific clusiid taxa are easily recognised but at species level, differences are relatively fine-grained and minor. A key is provided to identify puparia of species reared in this study.